2014
DOI: 10.2174/1871520614666140223192148
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic Acid as a Potent and Complex Antitumor Phytochemical: A Minireview

Abstract: Betulinic acid (BA), a natural compound with a lupan skeleton, has been highly investigated in the past decade for a plethora of beneficial properties, including anti-cancer, anti-inflammatory, anti-angiogenic, immune-modulatory, and anti-HIV effects. In particular, BA has been reported to be effective in vitro against tumor cell lines of different origins, and also in vivo, in animal models of cancer. The best characterized mechanism of its antitumor effect consists of triggering apoptosis via the mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 0 publications
1
52
0
Order By: Relevance
“…A tripchlorolide was shown to suppress the tumor cell growth and induce autophagic cell death in human lung cancer A549 cells, as well as in human neuroblastoma SH-SY5Y cells with no observed signs of apoptosis [179, 182, 183]. Betulinic acid is a triterpenoid isolated from the bark of the white birch tree, exhibited anticancer properties against several tumor cells in vitro and in vivo [184, 185]. Betulinic acid and its analogues were found to decrease the phosphorylation of AKT and induce autophagic cell death in human glioblastoma cells, as described in [186].…”
Section: Anticancer Natural Compounds and Autophagymentioning
confidence: 99%
“…A tripchlorolide was shown to suppress the tumor cell growth and induce autophagic cell death in human lung cancer A549 cells, as well as in human neuroblastoma SH-SY5Y cells with no observed signs of apoptosis [179, 182, 183]. Betulinic acid is a triterpenoid isolated from the bark of the white birch tree, exhibited anticancer properties against several tumor cells in vitro and in vivo [184, 185]. Betulinic acid and its analogues were found to decrease the phosphorylation of AKT and induce autophagic cell death in human glioblastoma cells, as described in [186].…”
Section: Anticancer Natural Compounds and Autophagymentioning
confidence: 99%
“…& Zeyh.) Kuntze [21] Roscovitine Antitumor, anticancer agent Raphanus sativus L. Plant-derived anticancer agents in preclinical development [22] Betulinic acid Anticancerous Betula alba Indian jujube-Ziziphus mauritiana Anemone -Anemone raddeana Club mosses-Lycopodium cernuum Trumpet satinash-Syzygium claviflorum [23] Bruceantin Anticancerous Brucea antidysenterica [24] Pervilleine A Anticancerous Erythroxylum pervillei Baillon [25] b-Lapachone Anticancerous Tabebuia serratifolia [26] 2-Cyano-3, 12-dioxoolean-1, 9-dien-28-oic acid (CDDO)…”
Section: Isolation Purification and Synthesismentioning
confidence: 99%
“…In the last decades, the biological activities and medicinal properties of BA have been intensively investigated; the results revealed that BA exhibits a plethora of beneficial properties, including anti‐tumour, anti‐angiogenic, anti‐inflammatory, anti‐fibrotic, anti‐HIV, and hepatoprotective effect . Furthermore, the most concerned activity of BA is anti‐tumoral activity currently, it has reported that BA shows significant cytotoxic on various tumour cell lines originating from lung, colon, prostate, and ovary, and in animal models in vivo . However, only a few papers on liver cancer were published.…”
Section: Introductionmentioning
confidence: 99%